A Criminological Outlook of Cyber Crimes in Sexual Violence Against Children in Indonesian Laws - Arsawati, I Nyoman Juwita; Darma, I Made Wirya; Antari, Putu Eva Ditayani (International Journal of Criminology and Sociology, 2021)
The purpose of this study is to analyze the cybercrimes in sexual violence against children in Indonesian laws. Act Number 11 of 2008 concerning Information and Electronic Transactions, concerning cybercrime specifically regulated in Indonesia. Of the various types of cybercrime that occur in Indonesia, it is interesting to study the vacuum norms governing cyber pornography carried out on children in Act Number 11 of 2008 concerning Information and Electronic Transactions. The crime can be said as violence against children whose punishment can be aggravated as stipulated in the Child Protection Act. This research is a normative legal study by examining the absence of norms in the ITE Law regarding sanctions imposed on perpetrators of child abuse in cyberspace. The study was conducted by using normative research methods so that utilizing primary legal materials such as the Criminal Code, Child Protection Act, Pornography Law, and Electronic Information and Transaction Law. Based on the collection and analysis of the legal material, the results showed that there is a need for criminal penalties for cyber pornography against children. This is done by considering the impact of the crime on the development of children and aims that the perpetrators deter and prevent similar crimes. The results practically contribute that the government is expected to play an active role in continuing to provide protection and assistance for psychological recovery from victims.